Faculty versus students: different perceptions of misconducts at university - Alcalde-Fradejas, Nuria; Marzo-Navarro, Mercedes; Ramírez-Alesón, Marisa (Frontiers in Psychology, 2024)
Academic integrity is a goal to be achieved by university institutions, and student academic behavioral misconduct is a phenomenon to be fought and eradicated. Two of the main problems faced by universities in this area are: 1) the lack of consensus among students and faculty on the seriousness of acts considered academic misconduct; and 2) the difficulty of noticing and controlling certain student behaviors. The main aim of this paper is to assess the importance of these two problems. For this purpose, the authors compare, on the one hand, students' and teachers' perceptions of the seriousness of different types of dishonest and inappropriate behaviors and, on the other hand, the frequency with which they report that these misconducts occur. Two samples were taken from the responses of students and teachers of the Economics and Business School of the University of Zaragoza. The first consisted of 333 students and the second of 72 teachers. The academic misconducts asked about were grouped into three categories: academic works, exams, and interpersonal relationships in the classroom. Nonparametric tests were used to study the significance of the differences observed in the responses of students and teachers. Results show that the greatest differences in the assessment of the seriousness of academic misconducts are in the group referring to interpersonal relationships. In terms of frequency, the study reveals that there is a serious problem of moral hazard in some of the behaviors analyzed, since the frequency with which teachers notice these practices is lower than that expressed by students. Based on these results, possible measures to be adopted in universities in order to eradicate the academic misconduct problem are discussed.